PERFORMANCE: Self, Management, and Organizational Social Perspectives - Anggraini, Fitria Nur (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Good work results are the hope of every leader, but in reality performance is not always achieved. Therefore, managers/directors need to make measurable efforts in encouraging performance improvement, including by making disciplinary rules, encouraging morale, and trying to create a healthy work environment. Based on this phenomenon, this study seeks to analyze the factors that affect performance. The research method used is quantitative with regression analysis. The research data was obtained by distributing questionnaires to 33 employees of Kopkar GMF Aero Asia Sejahtera. The sampling technique was carried out by simple random sampling. The results of the study explain that it is possible for employee performance to increase significantly both in partial and simultaneous models, especially in the discipline variable. Discipline rules are management products that are made to control measurable and quality work behavior, so as to maintain good task execution and quality results.